Synthesis and Application of Bis[1,2-(4-aryl-2-alkyl-1H- inden-1-yl)]Ethane as an Efficient`Ligand for Preparation of Olefin Polymerization Catalysts - v. Lotfi; B. Emamgholi; S. T. Bahrami; E. poorakbar (Journal of Sciences, Islamic Republic of Iran)
In this study, a class of bis-1,2-(4-aryl-2-alkyl-1H- inden-1-yl) ethane was synthesized and characterized by spectroscopic methods such as 1HNMR, 13CNMR, melting point and FTIR. bis-1,2-(4-aryl-2-alkyl-1H- inden-1-yl) ethane was synthesized by the reaction of butyllithium, arylindenes and dibromoethane in a facile, one-pot strategy. It’s shown that these methods have a wide scope to afford libraries of aryl-substituted indenes. The prepared compounds was then applied as a ligand for the fabrication of a number of metal complexes which can be used as catalyst for the polymerization of the olefins.